2006
DOI: 10.1021/es060827e
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Perfluorooctane Sulfonate and Other Perfluorinated Alkylated Substances in Harbor Porpoises from the Black Sea

Abstract: Perfluorooctane sulfonate (PFOS) and other perfluorinated alkylated substances (PFAS) were determined in liver, kidney, muscle, brain, and blubber samples of 31 harbor porpoises (Phocoena phocoena relicta) of different age and sex stranded along the Ukrainian coast of the Black Sea. In all individuals and in all tissues, PFOS was the predominant PFAS, accounting for on average 90% of the measured PFAS load. PFOS concentrations were the highest in liver (327+/-351 ng/g wet wt) and kidney (147 +/-262 ng/g wet wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 45 publications
8
44
0
Order By: Relevance
“…The mean PFOS levels found in the brain regions of the present polar bears ranged from 31.9 AE 5.9 to 58.8 AE 11.8 ng/g wet weight (Table 2). These brain levels were comparable to those found in recent studies on the brain of harbor porpoises (24 ng/g wet wt) off the coast of Ukraine [21] and the brain of harbor seals from the German Bight (99 ng/g wet wt) [17]. In the brains of avian species (glaucous gulls, pelicans) [22,24], PFOS concentrations have been found to be lower (<5 and 3.5 ng/g wet wt, respectively) than those in the current polar bear brain samples (Fig.…”
Section: Comparison With Pfcas and Pfsas In The Brains Of Other Studisupporting
confidence: 89%
See 2 more Smart Citations
“…The mean PFOS levels found in the brain regions of the present polar bears ranged from 31.9 AE 5.9 to 58.8 AE 11.8 ng/g wet weight (Table 2). These brain levels were comparable to those found in recent studies on the brain of harbor porpoises (24 ng/g wet wt) off the coast of Ukraine [21] and the brain of harbor seals from the German Bight (99 ng/g wet wt) [17]. In the brains of avian species (glaucous gulls, pelicans) [22,24], PFOS concentrations have been found to be lower (<5 and 3.5 ng/g wet wt, respectively) than those in the current polar bear brain samples (Fig.…”
Section: Comparison With Pfcas and Pfsas In The Brains Of Other Studisupporting
confidence: 89%
“…Harbor porpoise (1997-1998) [21] Harbor seal (2007) [17] Glaucous gull (2004) [24] Brown pelican (2004) [22] Fig been reported for polar bear liver, where the major PFCA was PFNA (C 9 ) [37,38]. This is a more pronounced shift than what was found in harbor seals [17], where there was a slight shift from C 9 being dominant in the liver to C 10 being dominant in the brain.…”
Section: Comparison With Pfcas and Pfsas In The Brains Of Other Studimentioning
confidence: 86%
See 1 more Smart Citation
“…The PFOS precursor N-EtFOSA itself was found in dolphins and porpoises from South China, [84] in whales from the Eastern Arctic [96] and in harbour seals from the German Bight. [18] Influence of age and sex on PFCs in marine mammals In general, in marine mammals no sex related differences in PFC concentrations were found (in seals, [71,72,80,83,97] in harbour porpoises, [85] in beluga whales, [98] in polar bears [87,99,100] ). In contrast, significant differences between males and females were reported in grey seals from the Baltic Sea, males having higher concentrations of PFOS than females.…”
Section: Pfc Pattern In Marine Mammalsmentioning
confidence: 99%
“…[17] In tissues of harbour porpoises (Phocoena phocoena relicta) from the Black Sea PFOS concentrations decreased from liver 4 kidney 4 muscle 4 brain 4 blubber. [85] Another study reported tissue distribution of PFCs in ringed seals (Phoca hispida) from Resolute Bay, Canadian Arctic, with highest PFOS concentrations in liver followed by lung, heart, spleen, blood, muscle and blubber. [86] An investigation of the total body burden and tissue distribution of 18 individual PFCs in harbour seals from the German Bight in 2007 resulted in decreasing PFOS concentrations in the following order: liver 4 lung 4 blood 4 thymus 4 kidney 4 heart 4 brain 4 muscle 4 thyroid 4 blubber.…”
Section: Spatial Distribution Of Pfcs In Marine Mammalsmentioning
confidence: 99%